A groupwise multiresolution network for DCE-MRI image registration - Strittmatter, Anika; Weis, Meike; Zöllner, Frank G. (Scientific reports, 2025)
In four-dimensional time series such as dynamic contrast-enhanced (DCE) MRI, motion between individual time steps due to the patient’s breathing or movement leads to incorrect image analysis, e.g., when calculating perfusion. Image registration of the volumes of the individual time steps is necessary to improve the accuracy of the subsequent image analysis. Both groupwise and multiresolution registration methods have shown great potential for medical image registration. To combine the advantages of groupwise and multiresolution registration, we proposed a groupwise multiresolution network for deformable medical image registration. We applied our proposed method to the registration of DCE-MR images for the assessment of lung perfusion in patients with congenital diaphragmatic hernia. The networks were trained unsupervised with Mutual Information and Gradient L2 loss. We compared the groupwise networks with a pairwise deformable registration network and a published groupwise network as benchmarks and the classical registration method SimpleElastix as baseline using four-dimensional DCE-MR scans of patients after congenital diaphragmatic hernia repair. Experimental results showed that our groupwise network yields results with high spatial alignment (SSIM up to 0.953 ± 0.025 or 0.936 ± 0.028 respectively), medically plausible transformation with low image folding (|J| ≤ 0: 0.0 ± 0.0%), and a low registration time of less than 10 seconds for a four-dimensional DCE-MR scan with 50 time steps. Furthermore, our results demonstrate that image registration with the proposed groupwise network enhances the accuracy of medical image analysis by leading to more homogeneous perfusion maps.